2015
DOI: 10.1371/journal.pone.0137403
|View full text |Cite
|
Sign up to set email alerts
|

The Conserved G-Protein Coupled Receptor FSHR-1 Regulates Protective Host Responses to Infection and Oxidative Stress

Abstract: The innate immune system’s ability to sense an infection is critical so that it can rapidly respond if pathogenic microorganisms threaten the host, but otherwise maintain a quiescent baseline state to avoid causing damage to the host or to commensal microorganisms. One important mechanism for discriminating between pathogenic and non-pathogenic bacteria is the recognition of cellular damage caused by a pathogen during the course of infection. In Caenorhabditis elegans, the conserved G-protein coupled receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 43 publications
1
58
0
Order By: Relevance
“…The G-protein coupled receptor (GPCR) FSHR-1 has been implicated in the survival of heavy metal and oxidative stress, as well as the innate immune response. Worms containing null mutations in fshr-1 have wild-type longevity under normal growth conditions, but have increased sensitivity to oxidative, heavy metal, and pathogen stresses [ 15 , 17 ] . Surprisingly these mutant worms are resistant to 2 °C cold shock (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The G-protein coupled receptor (GPCR) FSHR-1 has been implicated in the survival of heavy metal and oxidative stress, as well as the innate immune response. Worms containing null mutations in fshr-1 have wild-type longevity under normal growth conditions, but have increased sensitivity to oxidative, heavy metal, and pathogen stresses [ 15 , 17 ] . Surprisingly these mutant worms are resistant to 2 °C cold shock (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the G-protein coupled receptor FSHR-1 is required for the survival of exogenous oxidative stress and pathogen stress (infection). Infected fshr-1 null mutants fail to activate this ROS detoxification program, suggesting that FSHR-1 might be one link between the repair and recovery of oxidative stress and pathogen stress [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Like many invertebrates, C. elegans has a homolog of vertebrate glycoprotein receptors, which include TSH receptors. The ortholog FSHR-1 is involved in innate immunity, stress responses, and germline fertility (69)(70)(71). The C. elegans genome also encodes two genes, flr-2 and T23B12.8, for α and β glycoprotein subunits (72,73).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that microbial infections induce oxidative stress in C. elegans (Bolm et al, 2004;Miller et al, 2015;Sem and Rhen, 2012). We therefore treated worms with paraquat that is commonly used as an oxidative stress inducer (Senchuk et al, 2017).…”
Section: Endotube Dysfunction Correlates With Impaired Oxidative and mentioning
confidence: 99%